Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2020
DOI: 10.3350/cmh.2019.0051
|View full text |Cite
|
Sign up to set email alerts
|

Influence of some methylated hepatocarcinogenesis-related genes on the response to antiviral therapy and development of fibrosis in chronic hepatitis C patients

Abstract: Background/Aims: Epigenetics involved in multiple normal cellular processes. Previous research have revealed the role of hepatitis C virus infection in accelerating methylation process and affecting response to treatment in chronic hepatitis patients. This work aimed to elucidate the role of promoter methylation (PM) in response to antiviral therapy, and its contribution to the development of fibrosis through hepatocarcinogenesis-related genes. Methods: A total of 159 chronic hepatitis Egyptian patients versus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
4
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 27 publications
2
4
1
Order By: Relevance
“…Aberrant methylation of RASSF1A and p16 was detected in 32.6% and 28.6% of the cases, respectively. The observed frequencies of methylation in our study fit into the percentages reported in previous studies, which range from 16.2% to 68.4% for RASSF1A [17,36,37] and from 23.5% to 62% for the p16 gene [34,37], depending on the stage of the disease. Existing literature data indicate that the methylation of p16 and RASSF1A gradually increases with disease progression, with the highest levels detected in HCC [8,18,[36][37][38][39].…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Aberrant methylation of RASSF1A and p16 was detected in 32.6% and 28.6% of the cases, respectively. The observed frequencies of methylation in our study fit into the percentages reported in previous studies, which range from 16.2% to 68.4% for RASSF1A [17,36,37] and from 23.5% to 62% for the p16 gene [34,37], depending on the stage of the disease. Existing literature data indicate that the methylation of p16 and RASSF1A gradually increases with disease progression, with the highest levels detected in HCC [8,18,[36][37][38][39].…”
Section: Discussionsupporting
confidence: 90%
“…The observed frequencies of methylation in our study fit into the percentages reported in previous studies, which range from 16.2% to 68.4% for RASSF1A [17,36,37] and from 23.5% to 62% for the p16 gene [34,37], depending on the stage of the disease. Existing literature data indicate that the methylation of p16 and RASSF1A gradually increases with disease progression, with the highest levels detected in HCC [8,18,[36][37][38][39]. The methylation status of RASSF1A or p16 was not related to host factors, such as fibrosis, age and gender of patients.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…fatty liver) might be a contributing factor, the results of our study might indicate that anti‐HCV positivity, either by overt infection or past infection, might be significantly associated with higher fibrotic burden, which is the major determinant of long‐term prognosis. The progressive effect of HCV infection in terms of the development of chronic liver disease, cirrhosis, hepatic decompensation, and HCC is well known in the literature, 16–18 and careful observation should be undertaken in patients with progressed liver disease considering the risk of liver cirrhosis and HCC even after successful antiviral treatment 6,19–22 . Therefore, appropriate referral to a gastroenterologist is necessary for patients testing positive for anti‐HCV antibodies to enable proper evaluation, treatment, and follow‐up, which might improve their long‐term prognosis 20,21 …”
Section: Discussionmentioning
confidence: 99%